The effect of the successful intelligence strategy on the metacognitive skills of the third grade students at the Faculty of Education in the subject of teaching methods - Mantoub, Muhammad Kazim; Ali, Firas Trad (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the current research was that it came as a result of what the mechanism of studies calls at the present time, which is the development of the human mind in all its aspects, which comes through the path of successful intelligence education, which includes encouraging students to use their mental abilities and different thinking skills, in order to learn better, and to be given the opportunity to organize ideas and meanings It clarifies the relationships between the concepts included in a subject from the educational subject and helps students to organize their knowledge in order to deepen their understanding, and the current research aims to know the effect of the successful intelligence strategy on the achievement of the third grade students of the College of Education in the curriculum and framework Documents teaching. To achieve this, the researcher used experimental design with partial control consisting of two groups, one is experimental and the other is control, and the researcher intentionally chose Al-Muthanna University, College of Education, Department of History as a place to conduct the experiment, and the number of the sample (experimental and controlling) sample was (82) male and female students (42) male and female students (40) Male and female students. In a random manner, Division (b) was chosen as an experimental group that studies the strategy of successful intelligence, and the control group is taught in the usual way. Likewise, the scientific material was defined, behavioral goals were formulated and teaching plans were prepared. In line with the research goal, the researcher prepared a test of achievement of a multiple choice type, and the validity and reliability of the test as well as the statistical analysis of its paragraphs were confirmed. The results showed that using the T-test surpassed the experimental group that was studied according to the successful intelligence strategy over the control group that was studied in the usual way and in light of the research results, the researcher recommended the need to use the successful intelligence strategy as the researcher presented a set of recommendations and proposals, most notably conducting similar studies for the study Other current study levels. Also, to know the effect of using the successful intelligence strategy on other variables, such as critical thinking, innovative thinking, visual thinking, and visual perception.